Caenorhabditis elegans Neurotoxicity Testing: Novel Applications in the Adverse Outcome Pathway Framework - Sammi, Shreesh Raj; Jameson, Laura E.; Conrow, Kendra D.; Leung, Maxwell C. K.; Cannon, Jason R. (Frontiers in Toxicology, 2022)
Neurological hazard assessment of industrial and pesticidal chemicals demands a substantial amount of time and resources. Caenorhabditis elegans is an established model organism in developmental biology and neuroscience. It presents an ideal test system with relatively fewer neurons (302 in hermaphrodites) versus higher-order species, a transparent body, short lifespan, making it easier to perform neurotoxic assessment in a time and cost-effective manner. Yet, no regulatory testing guidelines have been developed for C. elegans in the field of developmental and adult neurotoxicity. Here, we describe a set of morphological and behavioral assessment protocols to examine neurotoxicity in C. elegans with relevance to cholinergic and dopaminergic systems. We discuss the homology of human genes and associated proteins in these two signaling pathways and evaluate the morphological and behavioral endpoints of C. elegans in the context of published adverse outcome pathways of neurodegenerative diseases. We conclude that C. elegans neurotoxicity testing will not only be instrumental to eliminating mammalian testing in neurological hazard assessment but also lead to new knowledge and mechanistic validation in the adverse outcome pathway framework.